Gene expression analysis and anti-WSSV property of antimicrobial peptides from the black tiger shrimp Penaeus monodon - Noppawan Woramongkolchai (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010